(untitled) (CIPEEX, 2025)
This paper analyzes the compatibility between the sovereignty of jury verdicts and setting aside convictions by means of the criminal review action, specifying when such an extraordinary remedy may be used without infringing the Jury Court’s constitutional remit. It employs a normative and case-law analysis grounded in Article 5, XXXVIII of the Brazilian Constitution, Article 621 of the Code of Criminal Procedure, and Supreme Court (STF) and Superior Court of Justice (STJ) precedents, to systematize the grounds and limits of post-final-judgment review. The findings indicate that sovereignty is not absolute and that criminal review, upon proof of serious error, false evidence, new facts or new evidence of innocence, does not replace the jurors’ assessment but corrects miscarriages of justice and may annul the verdict and order a new jury trial. It concludes that Brazilian law balances the authority of the Jury Court with the protection of fundamental rights, enabling the pursuit of the truth and the correction of unjust convictions without violating the sovereignty of verdicts.